2017
DOI: 10.1101/113209
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DHX15 regulates CMTR1-dependent gene expression and cell proliferation

Abstract: CMTR1 contributes to mRNA cap formation by methylating the O-2 position of the 1 st transcribed nucleotide ribose. mRNA cap O-2 methylation has roles in mRNA translation and self-RNA tolerance in innate immunity, however its role in cell physiology is unclear. We report that CMTR1 is recruited to Serine-5 phosphorylated RNA Pol II CTD, facilitating cotranscriptional methylation. We isolated CMTR1 in a complex with DHX15, an RNA helicase functioning in splicing and ribosome biogenesis, and characterised it as a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 51 publications
3
29
0
Order By: Relevance
“…These CMTR1 domains may provide a platform by which co-factors and post-translational modifications can mediate regulation of ribose O-2 methylation. The CMTR1 WW domain interacts with Ser-5 phosphorylated C-terminal domain (CTD) of RNA Pol II [ 77 , 78 ]. Since CMTR1 methylates G(5′)ppp(5′)X and m7G(5′)ppp(5′)X equivalently, it is possible that CMTR1 acts prior to RNMT [ 76 , 79 ].…”
Section: Mrna Capping Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…These CMTR1 domains may provide a platform by which co-factors and post-translational modifications can mediate regulation of ribose O-2 methylation. The CMTR1 WW domain interacts with Ser-5 phosphorylated C-terminal domain (CTD) of RNA Pol II [ 77 , 78 ]. Since CMTR1 methylates G(5′)ppp(5′)X and m7G(5′)ppp(5′)X equivalently, it is possible that CMTR1 acts prior to RNMT [ 76 , 79 ].…”
Section: Mrna Capping Enzymesmentioning
confidence: 99%
“…As described earlier, RNGTT is recruited to Ser-5 phosphorylated RNA Pol II CTD, and the guanylyltransferase activity is stimulated by this interaction [ 61 ]. CMTR1 is also recruited to Ser-5 phospho-CTD and RNMT is recruited to RNA pol II, probably indirectly, in a phospho-CTD-dependent manner [ 69 , 77 , 78 ]. Currently, there is no evidence that RNMT and CMTR1 are activated by interaction with the RNA pol II CTD.…”
Section: Major Cellular Mechanisms Of Mrna Cap Regulation In Mammalsmentioning
confidence: 99%
“…We also showed that hMTr1 interacts with RNA in vitro and with the C-terminal domain of the alpha subunit of RNA polymerase II using a yeast two-hybrid system. 8 Synthesis of mRNA requires the participation of a large set of proteins and ribonucleoprotein complexes that act cotranscriptionally to catalyze synthesis of the 5′-end cap, excision of introns, and polyadenylation of the 3′ terminus. Although the crystal structure described for hMTr1 6 revealed important details on the mechanism of action of this methyltransferase regarding its catalytic activity, there is scarce information about the interactions of hMTr1 with components of the RNA synthesis machinery.…”
mentioning
confidence: 99%
“…However, there is still no obvious evidence regarding their roles in regulating cartilage growth and development. DHX15 is a DEAH-box helicase involved in RNA processing, splicing, and ribosome biogenesis, which impacts gene expression and cell proliferation [62]. PKM is an enzyme responsible for the conversion of pyruvate and ATP in glycolysis, and plays a key role in regulating cell metabolism and proliferation [63].…”
Section: Discussionmentioning
confidence: 99%